Medial gastrocnemius flap: infection control in megaprostheses - Rana Kapukaya; Gazi Kutalmış Yaprak; Asena Ayça Özdemir; Ahmet Kapukaya (Journal of Plastic Surgery and Hand Surgery)
Introduction: Medial gastrocnemius flaps are commonly employed in conjunction with endoprosthesis implantations for the management of malignant tumors affecting the proximal segment of the tibia. This study aimed to evaluate the effect of the routine transfer of the muscle on the incidence of infections within the surgical field.